Một phương pháp xây dựng quan hệ thông tin không gian trong hệ thông tin địa lý véc tơ phân cấp - Hưng, Lê Quốc (Journal of Computer Science and Cybernetics, 2016)
This article describes the algorithm on building a relationship among point and line objects in a geographical information system (GIS) in order to make level chain and area objects of vector GIS. It also describes the method of linking those spatial objects and statistical data of the system. This algorithm has been applied by Insitute of Information Technology engineers into designing and setting up the PopMap geographical information system to the United Nations Department for Economic and Social Information and Policy Analysis.